Virucidal activity of nasal sprays against severe acute respiratory syndrome coronavirus-2. (February 2022) - Meister, T.L.; Todt, D.; Brüggemann, Y.; Steinmann, J.; Banava, S.; Brill, F.H.H.; Steinmann, J.; Pfaender, S.; Steinmann, E.
Summary: The highest viral loads of severe acute respiratory syndrome coronavirus-2 are detectable in the oral cavity, so a potential reduction of infectious virus by nasal and oral sprays could reduce transmission. Therefore, the inactivation capacity of nine nasal and oral sprays was evaluated according to EN 14476. One nasal spray based on sodium hypochlorite and one oral spray containing essential oils reduced viral titres by two to three orders of magnitude. Although clinical data are still sparse, nasal and oral sprays display a more convenient application for elderly people or those who are unable to rinse/gargle.